2013
DOI: 10.4103/0301-4738.111063
|View full text |Cite
|
Sign up to set email alerts
|

Relation between platelet indices and branch retinal vein occlusion in hypertensive patients

Abstract: Backgroud:Branch retinal vein occlusion (BRVO) is the second most common retinal vascular disease after diabetic retinopathy. To date, the studies were unable to elucidate the mechanism of the thrombosis leading to the entity; particularly the relation between thrombocyte aggregation and retinal vein occlusion is still unclear. Mean platelet volume (MPV) is a determinant of rate of platelet production and activation, both of which are indices of function of platelets. The relation between MPV and BRVO has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 25 publications
3
29
1
1
Order By: Relevance
“…Sahin et al showed higher levels of MPV in patients with RVO 26 . Önder et al found higher MPV levels in hypertensive BRVO patients 27 …”
Section: Discussionmentioning
confidence: 97%
“…Sahin et al showed higher levels of MPV in patients with RVO 26 . Önder et al found higher MPV levels in hypertensive BRVO patients 27 …”
Section: Discussionmentioning
confidence: 97%
“…Sistemik hastalıkların yanında oküler vasküler hastalıklarda da OTH ile hastalık ilişkisi çalışılmıştır. Retinal ven tıkanıklıkları ile OTH arasındaki ilişkiyi inceleyen çalışmalarda OTH değerlerinin kontrol olgularına göre daha yüksek olduğu saptanmıştır [5,14]. Bu çalışmalarda OTH'nin retinal ven tıkanıklıklarının tahmin edilmesinde belirteç olabileceği öne sürülmüştür.…”
Section: Introductionunclassified
“…In our study, the MPV values in RVO patients were also higher than in the control group but not statistically significant. However, a few studies reported that the MPV values were significantly higher in patients with RVO [18, 35], and inconsistent results were also reported where the MPV was significantly lower in patients with RVO than the control group [19]. Therefore, we expect future studies to confirm the relationship between MPV and patients with NVG secondary to RVO.…”
Section: Discussionmentioning
confidence: 84%